Estudio de factibilidad para implementación de sistemas fotovoltaicos y eólicos, en parques metropolitanos de Bogotá (2020)
Due to the indiscriminate exploitation and use of fossil fuels by human beings and the environmental problems generated as a result of this, the idea of ​​meeting energy demand through the use of alternative energy sources has been taken into account, which are a lot less degrading to the environment and to make humanity aware of the need to establish a world sustainable, in which favorable living conditions for future generations can be guaranteed. Studying the possibility of implementing technologies for the use of solar energy (solar panels) and wind energy (wind turbines) in urban public areas, specifically in parks on a metropolitan scale (large parks) in the city of Bogotá, makes it necessary to determine availability of solar and wind energy resources in the city, specify the electricity demand profiles in parks of this scale and choose the appropriate devices for the use of these energy resources. With this study, simulation models are obtained that allow integrating all the information collected, seeking to establish an optimal system architecture, capable of taking advantage of the energy resources available on site to generate electricity. The adaptation of renewable energy systems in metropolitan parks can greatly help Bogotá to advance towards sustainable energy development, which allows the city to occupy prestigious places worldwide regarding environmental issues. On the other hand, to explore the idea of ​​bringing the concept of rational and efficient use of energy closer to the daily life of human beings, through the implementation of energy capture devices in an area that represents part of the ecological structure of the city , hint the intention of wanting to use and produce electrical energy in a clean, efficient way and being consistent with the environment, which requires an energy model in which each individual, building and in this case large space, contributes to the energy consumption that society demands for its development.